Association Between Estuary Characteristics and Activities of the Critically Endangered Indo-Pacific Humpback Dolphin (Sousa chinensis) - Lin, Chi-hung; Lin, Hsing-Juh; Suen, Jian-Ping; Chou, Lien-Siang (Frontiers in Marine Science, 2021)
The Indo-Pacific humpback dolphin (Sousa chinensis) has been reported to prefer estuary habitats. This study explored the environmental factors affecting a critically endangered population off the coast of Yunlin, Taiwan. We measured dolphin sighting rates and estuary characteristics affected by the watershed, including seven physical factors (watershed rainfall, watershed runoff, estuarine turbidity, pH, salinity, temperature, and dissolved oxygen) and two biological factors (estuarine net primary production and chlorophyll a concentration), at the Hsinhuwei River estuary in Taiwan. Dolphin activity was measured by sighting rate and behavioral indices for feeding and traveling between 2017 and 2018. We observed that when the maximum net production increased alongside rising temperatures in spring, both the dolphin sighting rate and foraging activity increased. This trend was maintained until heavy rainfall or increased river runoff occurred during late summer, which resulted in high turbidity in autumn and winter. Turbidity was significantly negatively correlated with dolphin activity (sighting rate and foraging). Furthermore, we found that dolphin traveling positively correlated with the chlorophyll a concentration and maximum net production factors, which could attract dolphins expecting more abundant prey fish in the estuary supported by the high primary production. This study provides empirical evidence on how estuary characteristics affected by the watershed can affect the sighting rate and behavioral activities of Indo-Pacific humpback dolphins.